Implementasi Literasi Informasi dan Peran Perpustakaan dalam Sistem Pembelajaran di Pesantren Era Masyarakat Informasi - Ach. Nizam Rifqi (UIN Maulana Malik Ibrahim Malang, 2021)
This article discusses how to implement information literacy and the role of libraries in the learning system in pesantren. This writing is motivated by the development of technology and information which has also given birth to an information society that has brought significant developments in the world of education, including boarding schools. System education in pesantren is required to be able to produce students who are superior in the field of religion and produce those who have information literacy competence so that they can compete in the community. Pesantren library as a central source of information in this case has a central role as an information literacy agent in the pesantren environment. The organization of pesantren is required to be able to have several innovative activities and cooperate with the academic community of pesantren to develop activities in the pesantren learning system by incorporating elements of information literacy skills, especially for students.Keywords: Information Literacy, Pesantren Library, Pesantren Learning, Information Society.